TRADITIONS OF HEALING IN THE NATIONAL MEDICAL SYSTEM - DSc Khurshid Jumanazarov (Scholar Express Journal, 2025)
This article analyzes common treatment methods used by physicians in the national medical system. In accordance with the regional characteristics of the national medical system, doctors prescribe treatment measures taking into account the patient’s gender, age, profession and client. However, based on the type and specific characteristics of the disease, general treatment measures are also used.
Keywords: traditional medicine; tabib; bloodletting